My Twentieth Century: Zeitdiagnose and Modern Art in Badiou, Sloterdijk, and Stiegler - Miller, Tyrus (Filozofski vestnik, 2019)
Alain Badiou, Peter Sloterdijk, and Bernard Stiegler offered three distinct, but interrelated anatomies of the 20th century or, as Badiou expressed it, simply “The Century.” These included Badiou’s The Century, Sloterdijk’s You Must Change Your Life and What Happened in the Twentieth Century?, and Stiegler’s two-volume Symbolic Misery (I: The Hyperindustrial Epoch, II: The Katastrophē of the Sensible) and his related short book Acting Out. This paper considers their argument for the central role of art and aesthetics in the political, economic, cultural, and artistic legacy of the twentieth century, and their corollary arguments for the need to reconstruct and reorient our aesthetic understanding going forward into the post-20th-century future. It also highlights their discussions of the changing relationship between the subject of aesthetic experience and the subject of collective politics. Although each construes differently the specific content and causes of the 20th century mutation in subjectivity, as well as its aesthetic dimensions, they notably share a common focus and general structure of their Zeit-diagnostic arguments and prognostic conclusions.